Moving towards the Application of Biocatalysis in Food Waste Biorefinery - Sanjib Kumar Karmee (Fermentation, 2023)
Waste valorization is an important strategy to reduce environmental pollution and dependency on petroleum-based fuels. In this regard, utilization of food waste as a versatile and low-cost resource is important. Several advanced catalytic methods for the valorization of food waste have been widely investigated for the production of liquid biofuels. Along this line, chemical catalysts have been explored for the synthesis of liquid biofuels. Chemo-catalysis is mainly metal based, which requires harsh process conditions. Alternatively, biocatalysts are currently being investigated as a result of several advantages such as mild reaction conditions, recyclability, selectivity and biodegradability. In this work, recent biocatalytic technologies for the preparation of liquid biofuels through food waste valorization are discussed thoroughly. Lipases are employed for the synthesis of biodiesel and the upgradation of bio-oil, whereas methane mono-oxygenases could be explored for the production of methanol via the oxidation of methane generated from food wastes. Industrial production of ethanol from food waste using bioconversion technologies is a success story. To date, there has been no specific report on the use of food waste for propanol preparation using enzymes. The ABE process (Acetone–Butanol–Ethanol) (using suitable microorganisms) is used for butanol preparation, where the vacuum stripping system is integrated to remove butanol from the broth and circumvent inhibition. The synthesis of hydrocarbon fuels from fatty acids and triglycerides can be carried out using enzymes, such as carboxylic acid reductase and fatty acid photodecarboxylase (an algal photoenzyme). Both carboxylic acid reductase and fatty acid photodecarboxylase have not yet been applied in the direct valorization of food wastes. Furthermore, limitations of the reported methods, societal and economic aspects and a fresh perspective on the subject, along with important examples, are described.